1989
DOI: 10.1111/j.1365-2117.1989.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Extension and subsidence of the Pearl River Mouth Basin, northern South China Sea

Abstract: T h e uniform stretching model has been applied to seismic reflection profiles and well-log information from the Pearl River Mouth Basin on the northern flank of the South China Sea.Stretching factors were calculated from subsidence curves determined from the stratigraphy by using the backstripping technique to remove the effects of compactiori and sediment loading.Variations in rift topography, palaeobathymetry and global sea-level were taken into account. We argue that the Pearl River Mouth Basin formed by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…5) is marked by the red square Early Cretaceous (Taylor and Hayes 1980;Shi and Li 2012). In the latest Mesozoic and early Cenozoic, continental crust thinning and rifting occurred in the northern margin of the South China Sea (Taylor and Hayes 1983;Su et al 1989;Rangin and Silver 1991). Some failed rifts, such as the Xisha Trough filled with Paleocene and middle Eocene shallow marine sediments, was abandoned and subsided (Schlüter et al 1996).…”
Section: Geological Settingmentioning
confidence: 99%
“…5) is marked by the red square Early Cretaceous (Taylor and Hayes 1980;Shi and Li 2012). In the latest Mesozoic and early Cenozoic, continental crust thinning and rifting occurred in the northern margin of the South China Sea (Taylor and Hayes 1983;Su et al 1989;Rangin and Silver 1991). Some failed rifts, such as the Xisha Trough filled with Paleocene and middle Eocene shallow marine sediments, was abandoned and subsided (Schlüter et al 1996).…”
Section: Geological Settingmentioning
confidence: 99%
“…Furthermore, rifting was terminated during active propagation as result of the collision of the southern Dangerous Grounds margin with Borneo (Hutchison et al 2000;Clift et al 2008;Hinz et al 1989). This basin was formed as a result of extension starting in the Late Cretaceous and accelerating during the Eocene, culminating in breakup and the onset of seafloor spreading likely around 30 Ma, at least offshore of southern China (Su et al 1989;Briais et al 1993;Ru and Pigott 1986;Franke et al 2014;Barckhausen et al 2014). Studies of extension in this system, based on industrial seismic reflection profiles, suggested that the high degrees of subsidence seen, especially in the oceanward parts of the rifted margins around this basin could be explained in terms of depth-dependent extension (Davis and Kusznir 2004;Clift and Lin 2001).…”
Section: South China Seamentioning
confidence: 99%
“…5), algal organic matter with high 4-methyl sterane index. Between 32 and 30 Ma (during the deposition of E 3 e), climate in South China did not change much (Su et al, 1989;Jiang and Yang, 2000;Pang et al, 2009), but the intensity of rifting in the Zhu1 sub-basin was remarkably reduced. The reduced subsidence rate (202 m Ma À1 ) resulted in compensating sediment, shallower palaeo-water depth (compared to palaeowater depth during E 2 w deposition) and suboxic to oxic environments, leading to the deposition of E 3 e source rocks with relatively high terrigenous organic matter contribution characterized by high bicadinanes abundance.…”
Section: -Methyl Steranes Are Common Constituents Of the Cenozoic Lamentioning
confidence: 96%
“…During the deposition of E 2 w (56.5-32 Ma), widespread crustal thinning and normal faulting accompanied by uplift and erosion occurred and South China was then in warm and humid climate (Su et al, 1989;Jiang and Yang, 2000;Pang et al, 2009). The subsidence rate up to 290 m Ma À1 caused sediment starvation and the occurrence of deep-water, euxinic, anoxic environments, leading to the deposition of organic-rich (TOC contents up to 9.5%, Fig.…”
Section: -Methyl Steranes Are Common Constituents Of the Cenozoic Lamentioning
confidence: 98%
See 1 more Smart Citation